2003
DOI: 10.1093/emboj/cdg449
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of the M1 protein-binding domain of the influenza A virus nuclear export protein (NEP/NS2)

Abstract: contributed equally to this work During in¯uenza virus infection, viral ribonucleo proteins (vRNPs) are replicated in the nucleus and must be exported to the cytoplasm before assembling into mature viral particles. Nuclear export is mediated by the cellular protein Crm1 and putatively by the viral protein NEP/NS2. Proteolytic cleavage of NEP de®nes an N-terminal domain which mediates RanGTP-dependent binding to Crm1 and a Cterminal domain which binds to the viral matrix protein M1. The 2.6 A Ê crystal structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
229
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 189 publications
(235 citation statements)
references
References 55 publications
5
229
0
1
Order By: Relevance
“…3a and b) is suggestive of a possible role for NP. The conserved chemical nature of the amino acid residues between influenza type A and B NS2/NEP proteins suggests a common tertiary structure (Akarsu et al, 2003), which supports the hypothesis that both type A and B NS2/ NEP proteins are mediating the regulation of transcription and replication in a similar way.…”
Section: Discussionsupporting
confidence: 61%
See 4 more Smart Citations
“…3a and b) is suggestive of a possible role for NP. The conserved chemical nature of the amino acid residues between influenza type A and B NS2/NEP proteins suggests a common tertiary structure (Akarsu et al, 2003), which supports the hypothesis that both type A and B NS2/ NEP proteins are mediating the regulation of transcription and replication in a similar way.…”
Section: Discussionsupporting
confidence: 61%
“…Mutation of a tryptophan at residue 78 in the C terminus of the NS2/NEP protein, previously demonstrated to be critical for binding to M1 (Akarsu et al, 2003), did not affect the ability of NS2/NEP to regulate viral RNA levels (data not shown). In addition, fractionation experiments showed that the nuclear and cytoplasmic localization of viral RNA species was not altered by NS2/NEP and leptomycin B, an inhibitor of Crm1, did not alter the effect of NS2/NEP (data not shown).…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations